Refugee and Asylum-Seeking Children in Mae Sot and Bangkok: An Analysis of Unmet Needs and Risks. (11th December 2020) - Thoresen, Paradee; Gillieatt, Sue; Fielding, Angela
Abstract: This article reports on a longitudinal case study, which included site visits in Thailand from 2014 to 2015, and participant follow-up to mid-2018. It documents the lived experience of children from Syria, Sri Lanka, Pakistan, Vietnam, and Myanmar in two different locations in Thailand: Bangkok and Mae Sot (a district close to Thailand-Myanmar border with a long history of economic migrants and refugees from Myanmar). It documents perspectives of children and the adults in their lives while in exile. It presents an analysis of the children's perspectives on needs and how unmet needs for safety, basic materials, health care, and education put them at risk of arrest, detention, abuse, and exploitation, and impact their psychological development. Contextual factors such as available services, existing policies and laws are also discussed in relation to the Convention on the Rights of the Child (CRC).